2007
DOI: 10.1159/000111743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoride Compounds on Enamel Erosion in vitro: A Comparison of Amine, Sodium and Stannous Fluoride

Abstract: The aim of the study was to evaluate the relevance of cations in different fluoride compounds for their effectiveness as anti-erosive agents. Human enamel samples underwent a de- and re-mineralisation procedure for 10 days. Erosive demineralisation was performed with 0.05 Mcitric acid (pH 2.3) 6 × 2 min daily followed by immersion in the test solution 6 × 2 min each. Test solutions were: SnCl2 (815 ppm Sn; pH 2.6), NaF (250 ppm F; pH 3.5), SnF2 (250 ppm F, 809 ppm Sn; pH 3.5), amine fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
141
2
43

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(196 citation statements)
references
References 39 publications
10
141
2
43
Order By: Relevance
“…Thereby, SnF 2 containing toothpastes and solutions showed a better protective capability against erosion-like lesions than NaF agents. 10,11,23,24 Ganss et al 5 found that erosive mineral loss was nearly completely inhibited by AmF/SnF 2 and SnF 2 solutions, while NaF solutions were less effective and AmF and AmF/NaF showed no significant effect (all solutions: 250 ppm F -). The results of this study suggest that not only the fluoride, but also the respective cation could influence the protective efficacy of the fluoride compound.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, SnF 2 containing toothpastes and solutions showed a better protective capability against erosion-like lesions than NaF agents. 10,11,23,24 Ganss et al 5 found that erosive mineral loss was nearly completely inhibited by AmF/SnF 2 and SnF 2 solutions, while NaF solutions were less effective and AmF and AmF/NaF showed no significant effect (all solutions: 250 ppm F -). The results of this study suggest that not only the fluoride, but also the respective cation could influence the protective efficacy of the fluoride compound.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] As expected, in the present study, the profilometric analysis showed that the lowest tissue loss was observed in the fluoride-treated group (AmF/NaF/SnCl 2 solution containing 500 ppm F -, 800 ppm Sn 2+ , pH = 4.5) compared to the control group. The tin-containing solution was effective in inhibiting enamel surface loss in other in vitro 4,5,[28][29][30] and in situ 16,31 studies. The erosive tissue loss reduction caused by the fluoride solution (AmF/NaF/SnCl 2 ) compared to no treatment was 60%, which is very similar to the values currently published in the literature.…”
Section: Discussionmentioning
confidence: 86%
“…However, its efficacy is still the object of controversy 1,2 , because little is known about the mechanism of action of fluoride on the prevention and/or control of dental erosion; erosive challenges are much more aggressive than cariogenic challenges and only a thin surface layer, partially demineralized, remains to provide structure for remineralization of eroded surface. 1 Successful results on the reduction of dental demineralization by erosive acids have been shown with polyvalent metal ion-containing products, such as stannous, in several in vitro studies 3,4,5,6,7 and confirmed by other in situ studies. 8,9,10,11 Authors have reported the use of tin-ion in different presentation, such as solutions, toothpastes, gels and varnishes.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations